Geometrical Anatomy for Oxygen Vacancies in Epitaxial Hf0.5Zr0.5O2 Films Grown via Atomic Layer Deposition - Chihwan An; Jung Woo Cho; Tae Yoon Lee; Myeong Seop Song; Baekjune Kang; Hongju Kim; Jun Hee Lee; Changhee Sohn; Seung Chul Chae (Advanced Materials Interfaces)
Abstract The selective influence of elastic strain on the formation of oxygen deficiencies in (001)‐, (110)‐, and (111)‐ epitaxial Hf0.5Zr0.5O2 films grown by using atomic layer deposition is reported. Optical spectroscopy, conducted using UV–vis spectroscopic ellipsometry on these Hf0.5Zr0.5O2 films grown on yttria‐stabilized zirconia substrates, revealed a dominant shallow trap level in the (111)‐oriented Hf0.5Zr0.5O2 film. X‐ray photoemission spectroscopy demonstrated that the strong oxygen deficiency is preferred in the (111)‐oriented Hf0.5Zr0.5O2 film. Density functional theory calculations of oxygen vacancy formation energy also showed a pronounced preference for oxygen deficiencies in the (111) orientation. This selective formation of oxygen vacancies in the (111)‐oriented Hf0.5Zr0.5O2 film suggests that the latent phenomena associated with oxygen defects in functional Hf0.5Zr0.5O2 films are partly attributed to the directional strain in the (111) orientation.